The complete mitochondrial genome of a yeti crab Kiwa tyleri Thatje, 2015 (Crustacea: Decapod: Anomura: Kiwaidae) from deep-sea hydrothermal vent - Zhang, Dongsheng (Mitochondrial DNA B Resour, 2017)
The complete mitochondrial genome of Kiwa tyleri (Anomura, Chirostyloidea, Kiwaidae) was recovered by next generation sequencing. The mitogenome is 16,865 bp in length and contains 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), two ribosomal RNAs (rRNAs) and a 1525bp non-coding AT-rich region. This is the first mitogenome for the family Kiwaidae and the superfamily Chirostyloidea. The inversion of three consecutive genes (16S rRNA, tRNA-Val, 12S rRNA) was first reported for the Anomura. The phylogenetic tree indicated that Kiwaidae was close to Paguroidea and Lithodoidea rather than Galatheoidea.